Mapping the Evolution of Motifs in Indonesian Literature 1918-2025 Using Distant Reading - Martin Suryajaya; Hilmar Farid; Citra Smara Dewi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
This study presents a comprehensive overview of a century of Indonesian poetry, short stories, and novels in terms of the development of literary motifs, namely a series of words that are repeatedly deployed and serve as the formal basis of the theme. This study aims to address the scarcity in the scholarship of motifs in Indonesian literature over the long term by aiming to present a diachronic analysis of the changing meaning associations of the most frequently appearing motifs in Indonesian poetry and prose over the past century. This very broad scope does not hinder the analysis because this study uses digital humanities approach, specifically Franco Moretti's distant reading, which is a computational analysis of the statistics of word occurrences based on a digitized literary corpus. This paper analyzes a corpus of 193 award-winning or critically acclaimed Indonesian poetry and prose books (novels and short stories) published between 1918 and 2025, divided into 10 periods, each covering 11 years (with the exception of the final period, 2017-2025, which spanned 9 years). This paper addresses the following research question: is there a pattern underlying the evolution of motifs in Indonesian poetry and prose from 1918 to 2025? The findings of this study are: (1) there is a trend of increasing lexical diversity in Indonesian literature, (2) a number of words that are central motifs in Indonesian literature have experienced changes in their meaning associations to become more abstract, and (3) there are stylistic similarities between works based on similarities in motifs across periods.